PELATIHAN PRODUKSI “MULOHTEUPEH” PADA KELOMPOK USAHA KATERING PENAJOH ACEH DI DESA GLUMPANG BUNGKOK - Mujiburrahman, Mujiburrahman; Kamil, Ade Ikhsan; Akmal, Rifqi (PUAN INDONESIA, 2024)
This Article is carried out in the Gampong Glumpang Bungkok, Glumpang Baro District, Pidie Regency, Aceh. The location was chosen based on its uniqueness, including the special local knowledge, the level of fisheries resource production, and the significant impact of empowerment on the existence of the Peunajoh Aceh women's business group in Gampong Glumpang Bungkok. In order to improve the welfare of the members of the Peunajoh Aceh catering business group, the group should have a flagship product to compete in the culinary market. In reality, the group has not yet determined this flagship product, even though they have unique local knowledge about fish processing based on geographic indications. Therefore, a special treatment is needed in the form of revitalizing knowledge in the production of 'Muloh Teupeh' or boneless milkfish.